1997
DOI: 10.3109/00365529709025104
|View full text |Cite
|
Sign up to set email alerts
|

Plasma YKL-40: A New Potential Marker of Fibrosis in Patients with Alcoholic Cirrhosis?

Abstract: The increased plasma YKL-40 in patients with alcoholic cirrhosis may reflect the remodelling of liver fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 23 publications
2
66
0
Order By: Relevance
“…Other studies showed that serum YKL-40 level was positively related to the degree of liver fibrosis, and staining of YKL-40 was higher in areas with fibrosis, particularly in areas with active fibrogenesis (20,21). Along this line, it is possible that YKL-40 also plays a role in the tissue-remodeling process of asthma.…”
mentioning
confidence: 49%
“…Other studies showed that serum YKL-40 level was positively related to the degree of liver fibrosis, and staining of YKL-40 was higher in areas with fibrosis, particularly in areas with active fibrogenesis (20,21). Along this line, it is possible that YKL-40 also plays a role in the tissue-remodeling process of asthma.…”
mentioning
confidence: 49%
“…In prior studies, YKL-40 has been shown to be an excellent marker in active alcoholic liver disease. 28,41 Because we are using the markers for monitoring disease, the absolute levels are not as important as the rate of increase over time, and certainly YKL-40 and TGF-␤ in individuals show excellent sensitivity to disease progression. In fact, in the validation cohort, the sensitivity and specificity of YKL-40 for predicting disease progression was greater than 95% and represents one of the first cohort studies to really use longitudinal markers of serum fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[27][28][29][30] Schistosomiasis is a chronic helminthic disease infecting more than 200 million people worldwide. 31 Concomitant schistosomiasis and HCV infection is common in many developing countries 32,33 and exhibits a unique clinical, virological, and histological pattern manifested by virus persistence with high HCV RNA titers, higher necroinflammatory and fibrosis scores in liver biopsies, and poor response to interferon therapy.…”
Section: H Epatitis C Virus (Hcv) Infection Is Character-mentioning
confidence: 99%
“…For example, hypoglycemia (7 ) or physical exercise (8 ) are potent physiologic stressors, whereas fear (9 ), feelings of inferiority (10,11 ), or experiences at school (12,13 ) can affect the adrenal cortex activity as psychologic stressors. The taking of blood can also influence adrenal steroid concentrations in children; saliva collection, however, is almost stress-free (14 ).…”
Section: Ykl-40 As a Marker Of Joint Involvement Inmentioning
confidence: 99%